Pengaruh Proporsi Sepeda Motor terhadap Kinerja Ruas Jalan Tanpa Median : Studi Kasus : Jalan Sudirman Air Molek - Teguh Laksono; Sahriyal Sahriyal; Sri Guntur (Jurnal Sipil Terapan, 2023)
Motorcycles are a mode of transportation that is very commonly used in Indonesia. The large number of motorbikes on the road often causes congestion, because the ratio between the number of two-wheeled vehicles and four-wheeled vehicles when on the road becomes unbalanced. Passenger Car Equivalence Value for Motorcycles (MC) = 0.25 , Light Vehicles (HV) = 1.2 and Heavy Vehicles (LV) = 1.0. The influence of the Equivalence value of a motorcycle Passenger Car (emp) on the Degree of Saturation (DS) value, the smaller the Equivalence of a Passenger Car (emp), the smaller the Degree of Saturation (DS). The maximum degree of saturation (DS) occurs in the proportion of motorcycles 0.83%. And the influence of the proportion of motorcycles on Jalan Jendral Sudirman, Pasir Turtle District on Monday was 63.91%. while on Sunday the proportion of motorbikes was 65.37%.